Antenatal influenza and pertussis vaccination in Western Australia: a cross-sectional survey of vaccine uptake and influencing factors - Mak, Donna B. (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Influenza and pertussis vaccines have been recommended in Australia for women during each pregnancy since 2010 and 2015, respectively. Estimating vaccination coverage and identifying factors affecting uptake are important for improving antenatal immunisation services. METHODS: A random sample of 800 Western Australian women ≥18 years of age who gave birth between 4th April and 4th October 2015 were selected. Of the 454 (57%) who were contactable by telephone, 424 (93%) completed a survey. Data were weighted by maternal age and area of residence to ensure representativeness. The proportion immunised against influenza and pertussis was the main outcome measure; multivariate logistic regression was used to identify factors significantly associated with antenatal vaccination. Results from the 2015 study were compared to similar surveys conducted in 2012–2014. RESULTS: In 2015, 71% (95% CI 66–75) of women received pertussis-containing vaccine and 61% (95% CI 56–66) received influenza vaccine during pregnancy; antenatal influenza vaccine coverage was 18% higher than in 2014 (43%; 95% CI: 34–46). Pertussis and influenza vaccine were co-administered for 68% of the women who received both vaccines. The majority of influenza vaccinations in 2015 were administered during the third trimester of pregnancy, instead of the second trimester, as was observed in prior years. Women whose care provider recommended both antenatal vaccinations had significantly higher odds of being vaccinated against both influenza and pertussis (OR 33.3, 95% CI: 15.15–73.38). Of unvaccinated mothers, 53.6% (95% CI: 45.9–61.3) and 78.3% (95% CI: 70.4–85.3) reported that they would have been vaccinated against influenza and pertussis, respectively, if their antenatal care provider had recommended it. CONCLUSIONS: Pertussis vaccination coverage was high in the first year of an antenatal immunisation program in Western Australia. Despite a substantial increase in influenza vaccination uptake between 2014 and 2015, coverage remained below that for pertussis. Our data suggest influenza and pertussis vaccination rates of 83% and 94%, respectively, are achievable if providers were to recommend them to all pregnant women.